2014
DOI: 10.2478/adms-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Abrasion Resistance of Selected Biomaterials for the Friction Pairs in the Hip Joint Endoprosthesis

Abstract: The key requirement for the modern endoprosthesis is high durability of the friction components, which results in long and trouble-free operation in the human body. The durability of currently used endoprosthesis is often limited by tribological wear processes of friction components (e.g. between the head and the acetabular component in a hip joint endoprosthesis) [8,19,23,24]. In order to compare the tribological wear, tribological tests were carried out by means of tribometer on friction pairs of the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The analyses performed in the study revealed that the polyethylene insert represents the weakest component of the endoprosthesis [6,7]. The presented numerical analysis is the most efficient and clearest method to define distribution of stresses and strains present in components of hip and knee joint endoprostheses.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses performed in the study revealed that the polyethylene insert represents the weakest component of the endoprosthesis [6,7]. The presented numerical analysis is the most efficient and clearest method to define distribution of stresses and strains present in components of hip and knee joint endoprostheses.…”
Section: Introductionmentioning
confidence: 99%